Characteristics and health risks of benzene series and halocarbons near a typical chemical industrial park. (15th November 2021) - Chen, Ruonan; Li, Tingzhen; Huang, Chengtao; Yu, Yunjiang; Zhou, Li; Hu, Guocheng; Yang, Fumo; Zhang, Liuyi
Abstract: Health risks of typical benzene series and halocarbons (BSHs) in a densely populated area near a large-scale chemical industrial park were investigated. Ambient and indoor air and tap water samples were collected in summer and winter; and the concentration characteristics, sources, and exposure risks of typical BSH species, including five benzene series (benzene, toluene, ethylbenzene, o-xylene, m, p-xylene) and five halocarbons (dichloromethane, trichloromethane, trichloroethylene, tetrachloromethane, and tetrachloroethylene), were analysed. The total mean concentrations of BSHs were 53.32 μg m −3, 36.29 μg m −3, and 26.88 μg L −1 in indoor air, ambient air, and tap water, respectively. Halocarbons dominated the total BSHs with concentrations relatively higher than those in many other industrial areas. Industrial solvent use, industrial processes, and vehicle exhaust emissions were the principal sources of BSHs in ambient air. The use of household products (e.g., detergents and pesticides) was the principal source of indoor BSHs. Inhalation is the primary human exposure route. Ingestion of drinking water was also an important exposure route but had less impact than inhalation. Lifetime non-cancer risks of individual and cumulative BSHs were below the threshold (HQ = 1), indicating no significant lifetime non-cancer risks in the study area. However, tetrachloromethane, benzene, trichloromethane, ethylbenzene, and trichloroethylene showed potential lifetime cancer risk. The cumulative lifetime cancer risks exceeded the tolerable benchmark (1 × 10 −4 ), indicating a lifetime cancer risk of BSHs to residents near the chemical industry park. This study provides valuable information for the management of public health in chemical industrial parks. Graphical abstract: Image 1 Highlights: Benzene series and halocarbons (BSHs) were the main VOCs in a large industry park. Industry and vehicle exhaust were the principal sources of BSHs in ambient air. BSH health risk was higher for inhalation than for ingestion. Cumulative lifetime cancer risk of BSHs exceeded the tolerable benchmark.